Pengaruh Pelatihan dan Motivasi terhadap Kompetensi Serta Dampaknya pada Kinerja Guru SMA Negeri 1 Batang Hari - Teguh Okni Pratama; M. Zahari MS; Osrita Hapsara (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to find out how the influence of training and motivation at SMA Negeri 1 Batang Hari has on the level of competence and quality of teacher work. The data population for this study were 62 educators at SMA Negeri 1 Batang Hari, and the researchers used a quantitative descriptive approach, path analysis and simultaneous F-test hypothesis testing using the assistance of the IBN SPSS Version 20 program. Through path analysis it was found that the total effect the influence of training (X1) and motivation (X2) through competence on teacher performance (Z), has a total value of 97.99%. The results of the simultaneous F test on competency training variables stated that H0 was rejected and H1 was accepted, meaning that the training and competency variables had an effect on teacher performance, and also on the motivational variable on teacher performance through competence stated that H0 was rejected and H1 was accepted, meaning that training and motivation variables had an effect on performance. teacher at SMA Negeri 1 Batang Hari.